Ciencia, tecnología e innovación. como motor de desarrollo económico : el caso de la Región Caribe colombiana (2014)
In recent years, the importance of Science, Technology and Innovation (STI) for the long term economicdevelopment has gain an important recognition specially in the public, private and academic spheres. Public STI policies play now, more than ever, an important role in the public policy especially in developed economies. Even though Colombia has implemented some strategies to strengthen STI, the indicators still show important deficiencies compaired to international standards, and, internally, there is evidence of regional disparities. The aim of this article is to identify and explain the lag of the Caribbean Region in terms of investment in STI activities as well as to analize its evolution in comparison with other regions.